Influence of ultrasound extraction of Fucus vesiculosus on the kinetics of fucoidan degradation and its properties - E. D. Obluchinskaya; O. N. Pozharitskaya (Разработка и регистрация лекарственных средств, 2025)
Introduction. A promising source for isolating fucoidan is Fucus vesiculosus L., a widespread species of brown algae. In recent years, the possibility of using fucoidan in medicine and pharmacy has been widely studied. The method of extracting polysaccharides significantly affects their characteristics and properties. To improve extraction efficiency, the possibility of using ultrasonic-assisted extraction (UAE) has recently been widely explored.Aim. Study of the influence of the time of low-frequency UAE of brown algae F. vesiculosus on the kinetics of fucoidan degradation and its properties.Materials and methods. Fresh frozen brown algae F. vesiculosus L. were used as raw material. UAE was carried out at an oscillation frequency of 22 kHz and a temperature of 25 °C. The extract was obtained at a temperature of 60 °C using the dynamic maceration method. The homogeneity and molecular weight of fucoidan were analyzed by high-performance size exclusion chromatography (HPSEC). FT-IR spectra of fucoidan were obtained on a VERTEX 70 spectrometer. Quantitative determination of fucose and sulfates was performed using a spectrophotometric method. The antioxidant activity (AOA) of fucoidan was assessed using FRAP test. Mathematical and statistical processing of the results was carried out in accordance with Russian Federation Pharmacopeia XV edition using MO Excel 2007 software.Results and discussion. The calculated rate of fucoidan degradation was 19.5 %/h. The reaction rate constant and half-life calculated using the second-order model (R2 > 0.97) were 5.8 · 10–6 mol/(g · min) and 110 min. Ultrasonic degradation of fucoidan occurred predominantly due to random scission model (R2 > 0,98). Using FTIR spectrometry, it was found that the preliminary structures of fucoidan without ultrasound and after ultrasound extraction were not changed. Analysis of antioxidant activity showed that fucoidan after ultrasonic extraction, despite a decrease in molecular weight, demonstrated significant antioxidant activity in vitro.Conclusion. For the first time, a change in the conformational and antioxidant properties of fucoidan caused by low-frequency UAE was shown. UAE of fucoidan leads to a decrease in average molecular weight and degradation of fucoidan without significant destruction of sulfate groups. Overall, this study shows that the low frequency ultrasonic extraction, which is a gentle, environmentally friendly method that can be completed in a short period, can be effectively used to extract fucoidan without critically changing the molecular weight and antioxidant activity.